The incidence, comorbidity and mortality of sarcoidosis in Korea, 2008-2015: a nationwide population-based study - Jeon, Mi Hye; Kang, Taeuk; Yoo, Sang Hoon; Swan, Heather S; Kim, Hyun Jung; Ahn, Hyeong Sik (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Few national level, population-based studies are present on the epidemiology of sarcoidosis and it is unclear whether these patients have higher mortality than the general population. The objective of this study was to investigate the nationwide epidemiology, comorbidity and mortality in sarcoidosis in Korea. Material and Methods: For the period between 2008 to 2015, we used the national population-based database operated by Rare Intractable Disease registration program in which patients’ diagnosis are based on uniform criteria. All sarcoidosis patients were identified and followed-up using the National Health Insurance database to determine their incidence, comorbidity, mortality, causes of death and standardised mortality ratio (SMR). Results: During the study period, we identified 3,259 new sarcoidosis patients. The average annual incidence was 0.81 per 100,000. The annual mortality rate was 9.26 per 1,000 person-years. The mortality rate were significantly higher than those of the general population (SMR 1.91, 95% confidence interval 1.62-2.25). The major comorbidities of sarcoidosis patients were the diseases of the respiratory system (17.64%), heart (5.43%), eyes (4.27%) and cancer (2.3%). Mortality was higher in patients with lung involvement. Of the 84 deaths identified in this study from 2008-2013, the most common cause of death was cancer (41.7%), followed by respiratory disease (13.1%), sarcoidosis (13.1%) and heart disease (8.3%). Conclusions: We reported a nationwide incidence of sarcoidosis as 0.81 per 100,000 in Korea. The mortality of sarcoidosis patients was higher compared to the general population and the major causes of death were cancer, respiratory disease and sarcoidosis. Sarcoidosis patients with comorbid diseases showed increased mortality.